Solve the quadratic equation (x+6) (x-4) = 0 using the zero product property

1 answer

To solve the quadratic equation \((x + 6)(x - 4) = 0\) using the zero product property, we set each factor equal to zero.

  1. Set the first factor equal to zero: \[ x + 6 = 0 \] Subtracting 6 from both sides gives: \[ x = -6 \]

  2. Set the second factor equal to zero: \[ x - 4 = 0 \] Adding 4 to both sides gives: \[ x = 4 \]

Thus, the solutions to the equation \((x + 6)(x - 4) = 0\) are: \[ x = -6 \quad \text{and} \quad x = 4 \]